IDENTIFYING THE USE OF QUIZZES FOR STUDENTS DURING ONLINE LEARNING - Rahmad Risan (Universitas Suryakancana, 2021)
The purpose of this study is to identify the use of quizzes for students during online learning. This research is descriptive qualitative research. Data will be collected through questionnaires and interviews on research subjects. The data collected will be analyzed qualitatively to describe the phenomena that occur in the field. Based on data from the research results, there are 47 students (29%) who chose E-learning quiz as a quiz that they often use.; 34 students (22%) who chose Quizizz; 30 students (18%) who chose Google Form Quiz; 23 students (14%) who chose quiz on the website as a quiz that they often get / use in learning; 19 students (11%) who choose Kahoot as a quiz that they often get / use in learning; and five students (3%) who choose Wondershare Quiz Creator as a quiz they often get / use in learning. This study proves that all types of quizzes are very helpful for students to review previous learning materials. In addition, this quiz can attract students to increase the duration of study at home.Keywords: Identification, Quiz, Online Learning